Social Work and Elder Abuse: A Foucauldian Analysis - Jason L. Powell (Social Work and Society, 2012)
Recently, there an accelerating interest in elder abuse has arisen due to the implementation of community care policies relying upon informal care and a relentless political campaign to legitimise an enforced obligation to care. The use of care management technologies that focus on assessment and inspection, can, in this policy climate, become a means of surveillance and enforcement of informal caring. It is argued that Michel Foucault offers a set of strategies (Foucault 1977: 205) for understanding how the discourses on community care construct older people's experiences and their identities, as constructed subjects and objects of managerial knowledge.